Germline BRCA mutation does not prevent response to taxane-based therapy for the treatment of castration-resistant prostate cancer - Gallagher, David J. (2011)
OBJECTIVE: To investigate the relationship between BRCA mutation status and response to taxane-based chemotherapy, since BRCA mutation carriers with prostate cancer appear to have worse survival than non-carriers and docetaxel improves survival in patients with castration-resistant prostate cancer. PATIENTS AND METHODS: We determined BRCA mutation prevalence in 158 Ashkenazi Jewish (AJ) men with castration-resistant prostate cancer. Clinical data were collected as part of an institutional prostate cancer research database and through additional medical record review. Clinical records and DNA samples were linked through a unique identifier, anonymizing the samples before genetic testing for the AJ BRCA1/2 founder mutations. Response to taxane-based therapy was defined by the prostate-specific antigen nadir within 12 weeks of therapy. RESULTS: In all, 88 men received taxane-based treatment, seven of whom were BRCA carriers (three BRCA1, four BRCA2; 8%). Initial response to taxane was available for all seven BRCA carriers and for 69 non-carriers. Overall, 71% (54/76) of patients responded to treatment, with no significant difference between carriers (57%) and non-carriers (72%) (absolute difference 15%; 95% confidence interval −23% to 53%; P = 0.4). Among patients with an initial response, the median change in prostate-specific antigen was similar for BRCA carriers (−63%, interquartile range −71% to −57%) and non-carriers (−60%, interquartile range −78% to −35%) (P = 0.6). At last follow-up, all seven BRCA carriers and 49 non-carriers had died from prostate cancer. One BRCA2 carrier treated with docetaxel plus platinum survived 37 months. CONCLUSION: In this small, hypothesis-generating study approximately half of BRCA carriers had a prostate-specific antigen response to taxane-based chemotherapy, suggesting that it is an active therapy in these individuals.